Simulation and zoning evaluation of in-situ stress field within ultra-deep tight sandstone reservoirs in thrust-nappe structures of Bozi-Dabei area, Tarim Basin - Zimeng XING; Ruixue LI; Hucheng DENG; Hang SU; Jiawei ZHANG; Jianhua HE; Hui ZHANG; Xiaofei HU; Shunting MA (Shiyou shiyan dizhi)
The Cretaceous tight sandstone reservoirs in the Bozi-Dabei area of the Tarim Basin are key targets for ultra-deep tight sandstone gas exploration and development in China. Influenced by thrust-nappe structures and salt structures, the region has formed imbricate folding structures and a series of faults with large displacements and varying dip angles, resulting in a complex and highly variable in-situ stress field that is difficult to predict, severely restricting exploration and development in the area. To clarify the stress distribution pattern, an in-situ stress field simulation method, suitable for the characteristics of thrust-nappe structures was developed. Moreover, a stress grading and zoning evaluation was conducted, combining with the geological and engineering modification characteristics of the reservoirs. Core testing, well logging, and mining field test data were used to calibrate the in-situ stress direction and magnitude for individual wells, and their distribution characteristics were analyzed. By examining the impact of in-situ stress on reservoir physical properties, brittleness, and engineering modification difficulty, stress grading evaluation standards for the study area were established. A detailed three-dimensional heterogeneous in-situ stress field model was constructed for well B1, a key development area in the Bozi-Dabei area, to clarify the stress distribution characteristics and conduct zoning evaluations. The average error rate between the numerical simulation results and single-well in-situ stress interpretations was less than 10%. In well B1, the in-situ stress direction was primarily between N170°-190°E, and the stress direction near the faults deflected along the fault strike with deflection angles ranging from 20° to 60°. The magnitude of in-situ stress increased from north to south with burial depth, with reduced in-situ stress and stress differences at the high point of the anticline and within the fault zone. The higher the fault order, the greater the disturbance range and intensity. Based on a minimum principal stress of 145 MPa and a horizontal stress difference of 34 MPa, the in-situ stress state was classified into four categories: low stress difference with low in-situ stress, high stress difference with low in-situ stress, low stress difference with high in-situ stress, and high stress difference with high in-situ stress. The low stress difference and low in-situ stress areas in well B1, which are favorable for fracturing modification, are mainly developed in the hanging wall of the faults in the Cretaceous Bashijiqike Formation (K1bs) and the high structural deformation areas.